Toxicological and biochemical effects of some insecticides on peach fly, Bactrocera zonata (Diptera: Tephritidae) - Yahia Youssef Mosleh; Lamiaa Housein Yousry; Adel Abo-El-Elaa (Plant Protection Science, 2011)
The peach fruit fly, Bactrocera zonata (Saunders, Diptera: Tephritidae), has been a serious pest in the last decade attacking a wide range of fruits in Egypt. The toxicity of Malathion, Diazinon, Methoxyfenozide and Lufenuron to adult males and females of B. zonata was studied under laboratory conditions. The results showed that Diazinon was the most toxic among the tested compounds followed by Malathion, Lufenuron and Methoxyfenozide. LC50 values for adult males and females were 0.20 ppm, 0.09 ppm and 0.02 ppm (for males), 0.91 ppm, 0.14 ppm and 0,01 ppm (for females), respectively. The results showed that the level of glutamic oxaloacetic transaminase (GOT) of treated adult males and females in 24 h, 48 h, and 72 h post treatment increased compared to untreated adults. The highest activities of GOT in treated adult males in 24 h, 48 h, and 72 h were 92.11µM, 101.99µM and 112.21µM pyruvate released × 103/min/g FW (fresh weight), respectively, for Methoxyfenozide LC10, and in treated adult females after 24 h, 48 h, and 72 h they were 84.24µM, 94.33µM, and 111.12µM pyruvate released × 103/min/g FW, respectively, for Diazinon LC25. The activities of acetylcholine esterase of treated adults decreased compared to untreated adults. The highest activities of acid phosphatase in adult males after 24 h and 48 h were 249.43 µg and 270.52 µg AchI hydrolysed/min/g FW, respectively, for Methoxyfenozide LC25. The highest activities of alkaline phosphatase in adult males were 139.04 µg, 175.67 µg, and 199.29 µg phenol × 103/min/g FW for Malathion LC10 and in adult females they were 123.31 µg, 162.10 µg and 199.59 µg phenol.103/min/g FW, respectively, for Lufenuron LC25 in 24 h, 48 h, and 72 h post treatment.